If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying w + 12 = 8 Reorder the terms: 12 + w = 8 Solving 12 + w = 8 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + w = 8 + -12 Combine like terms: 12 + -12 = 0 0 + w = 8 + -12 w = 8 + -12 Combine like terms: 8 + -12 = -4 w = -4 Simplifying w = -4
| 63-14x=72 | | 63-14=72 | | 51-4x=14x+7 | | 4x+9=-79x-7x | | 2x-3x-8x-3=0 | | 6n-18=4n+8.4 | | 3x+1=b | | 14t=8 | | 7+2x+2=2x+9 | | 5x+6-3= | | 8x^2-14x-5=0 | | 2a+4-8a-10= | | 5x+4=7x+7-2x | | 2x+38=x+29 | | 1.20=0.20x+0.40 | | 42-3x=6x+19 | | 219-4x=32x+15 | | 1.90=0.30x+0.40 | | 2(4x-3)=3(x-1) | | -1-6x=11-10 | | 6(r+2)-4=10 | | 12x+4=4x+5 | | 9x+5y=47 | | 2b/3+6=24 | | 13x+2=6x+15 | | 9r+5=24+10r | | -8.4=-6 | | 2x+2-10=12 | | 4k-6=k+12 | | 0*0= | | 3c+5c=32 | | 105-2x=34x+17 |